Zenon z Elei – doksografia i fragmenty (Zeno of Elea – doxography and fragments) - Wesoły, Marian (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2013)
After a very general exegetical introduction, we put forward a new arrangement and translation of the major testimonies on Zeno of Elea. The few passages that are generally regarded as fragmenta verbatim are also cited in the original. The source material is presented in a reconstructive order that is somewhat different from the previous editions of Zeno. Our aim is to capture the specific problematic context of the ancient authors who refer and question Zeno’s arguments, without isolating and break up theses texts. The particular passages have been provided with thematic headings.